Desinformação como ferramenta de poder em plataformas de mídia social: uma reflexão à luz do pensamento foucaultiano - Silva, Eliana Pegorim Abreu e; Bastos Faria Pecoraro, Caroline (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2024)
Even 40 years after his death, Michel Foucault remains current and contemporary in his discussions, concepts and reflections. Although disinformation is not an exclusive contemporary phenomenon, it is clear that it constitutes a chronic and unique problem in today's society due to its configuration on social media platforms. This essay proposes a reflection on the problem of disinformation on social media platforms in the light of Foucauldian thought. Based on theoretical discussion and a survey of empirical studies, the essay deals with the political use of disinformation as a tool of power in today's society and how Foucault's thinking can bring us a theoretical framework for reflecting on the ways in which disinformation and disinformative narratives work.